Network Model Diversity For Wireless Studies - Nahar, Haniza; Sahib, Shahrin; Muslim, Zulkiflee; Ayop, Zakiah (JICT, 2013)
Wireless network is one of interesting research domain. Many studies have been conducted related to security and network performance issue. There are two methods to represent a conducting study either based on test bed or simulation in order to access the real network environment. With a suitable network model selection, any research might achieve its objective. Therefore, this paper provides a collection of network models that has been used particularly in wireless network to assist researchers on selecting an appropriate network model for their conducting study. The result gathered from various technical and theoretical research papers. In future, the intention on more generic justification of selective parameters to be used for wireless study will be shared later on.